1999
DOI: 10.2337/diacare.22.12.2072
|View full text |Cite
|
Sign up to set email alerts
|

Impaired diurnal cardiac autonomic function in subjects with type 2 diabetes.

Abstract: These data indicated that diabetic subjects with peripheral neuropathy and diabetic subjects with symptomatic autonomic neuropathy, but not diabetic subjects without neuropathy, showed a marked decrease in cardiac sympathetic and parasympathetic nerve functions and loss of circadian rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
0
12
1
2
Order By: Relevance
“…Sayer et al (39) found that the rhythm of sympathovagal balance was significantly attenuated in patients with diabetes compared with those without diabetes. Similarly, patients with diabetes and symptomatic autonomic neuropathy have been shown to have markedly impaired heart rate variability (40,41). Lower heart rate variability in turn has been shown to be associated with an increased risk of development of coronary heart disease in individuals with diabetes (42).…”
Section: Discussionmentioning
confidence: 99%
“…Sayer et al (39) found that the rhythm of sympathovagal balance was significantly attenuated in patients with diabetes compared with those without diabetes. Similarly, patients with diabetes and symptomatic autonomic neuropathy have been shown to have markedly impaired heart rate variability (40,41). Lower heart rate variability in turn has been shown to be associated with an increased risk of development of coronary heart disease in individuals with diabetes (42).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating that SCN functioning is affected in several chronic diseases, such as hypertension, diabetes and depression. For a long time now physiological studies have indicated disturbances in the circadian rhythm in patients suffering from these diseases (Pickering 1990, Yamamoto et al 1999. Recently, we demonstrated the anatomical basis for these disturbances in hypertensive patients: a severe decrease in staining for several SCN neurotransmitters (Goncharuk et al 2001) (Fig.…”
Section: The Human Scnmentioning
confidence: 99%
“…As shown in Table 1, there was a 4% increase of R-%LF after acute insulin infusion. This may seem a small change, but we previously found that the relative increase of mean %LF between 0800 and 1200 compared with the daily mean %LF (0800-0800) was 4-6%, whereas no significant increase was detected in subjects with diabetic autonomic neuropathy (21). Accordingly, the modest increase of R-%LF observed in the present study may be physiologically meaningful.…”
Section: Discussionmentioning
confidence: 39%
“…Although the LF-to-HF ratio has been suggested as a marker of SNA, we have shown that the LF/(LF ϩ HF) ratio is an alternative marker (22). We have also reported that type 2 diabetics with symptomatic autonomic or peripheral neuropathy, but not diabetics without neuropathy, show a decrease of both the LF and HF components and loss of the normal circadian rhythm of heart variability (21).…”
mentioning
confidence: 57%
See 1 more Smart Citation